Undivided rights: Women of color organizing for reproductive justice - Silliman, Jael; Fried, Marlene Gerber; Ross, Loretta; Gutiérrez, Elena (Haymarket Books, 2016)
Undivided Rights captures the evolving and largely unknown activist history of women of color organizing for reproductive justice—on their own behalf.Undivided Rights presents a textured understanding of the reproductive rights movement by placing the experiences, priorities, and activism of women of color in the foreground. Using historical research, original organizational case studies, and personal interviews, the authors illuminate how women of color have led the fight to control their own bodies and reproductive destinies. Undivided Rights shows how women of color—-starting within their own Latina, African American, Native American, and Asian American communities—have resisted coercion of their reproductive abilities. Projected against the backdrop of the mainstream pro-choice movement and radical right agendas, these dynamic case studies feature the groundbreaking work being done by health and reproductive rights organizations led by women-of-color.The book details how and why these women have defined and implemented expansive reproductive health agendas that reject legalistic remedies and seek instead to address the wider needs of their communities. It stresses the urgency for innovative strategies that push beyond the traditional base and goals of the mainstream pro-choice movement—strategies that are broadly inclusive while being specific, strategies that speak to all women by speaking to each woman. While the authors raise tough questions about inclusion, identity politics, and the future of women’s organizing, they also offer a way out of the limiting focus on "choice."Undivided Rights articulates a holistic vision for reproductive freedom. It refuses to allow our human rights to be divvied up and parceled out into isolated boxes that people are then forced to pick and choose among.
Keywords: afro-féminisme; amériques; approches et analyses; discours dominant; droits des femmes*; histoire et politique; intersectionnalité; inégalités; justice reproductive; militance; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis

Andropause et ménopause : la sexualité sur ordonnance - Moulinié, Véronique (Clio. Femmes, Genre, Histoire, 2013)
L’invention de la ménopause au xixe siècle puis celle de l’andropause dans la seconde moitié du xxe siècle ont eu pour effet d’accroître la surveillance des médecins sur les corps féminins et masculins vieillissants et, plus spécialement, sur la sexualité de cette période de la vie. Or, si ce coup d’état médical a si bien réussi, c’est qu’il a tout autant bénéficié du soutien très actif des femmes que de l’incapacité des hommes à lui résister. C’est aussi qu’il s’inscrivait dans le prolongement de très anciennes pratiques sociales qu’il légitimait. Et qu’on ne s’y trompe pas. Loin de se desserrer, l’étau s’est définitivement refermé. En effet, les hommes, qui ont longtemps tenté d’échapper maladroitement à cette surveillance, ont, aujourd’hui, fini par s’y soumettre, acceptant, de fait, tout le discours silencieux sur les défaillances de leur puissance virile qu’elle suppose.
ISBN: 9782701177816 Number: 37 Publisher: Éditions Belin
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexisme; inégalités; justice reproductive; premier cycle; privilèges; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

Une médecine féministe. Entretien avec Emmanuelle Piet - Andro, Armelle; Hamel, Christelle (Nouvelles Questions Féministes, 2010)
Number: 3
Keywords: 1900-1999; 1970-1979; approches et analyses; corps; cours; discipline; discours dominant; europe; france; inégalités; justice reproductive; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; violences